2014
DOI: 10.1128/aac.01605-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Klebsiella sp. Strain 10982, a Colonizer of Humans That Contains Novel Antibiotic Resistance Alleles and Exhibits Genetic Similarities to Plant and Clinical Klebsiella Isolates

Abstract: A unique Klebsiella species strain, 10982, was cultured from a perianal swab specimen obtained from a patient in the University of Maryland Medical Center intensive care unit. Klebsiella sp. 10982 possesses a large IncA/C multidrug resistance plasmid encoding a novel FOX AmpC ␤-lactamase designated FOX-10. A novel variant of the LEN ␤-lactamase was also identified. Genome sequencing and bioinformatic analysis demonstrated that this isolate contains genes associated with nitrogen fixation, allantoin metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…In this work, we identified another K. pneumoniae genome (from KPNIN29) that contains the nif operon in addition to that described by Holt and colleagues. 13 Hazen and colleagues 27 identified the absence of nifJ-nifQ gene cluster in K. pneumoniae NTUH-K2044, MGH-78578, 1162281, JH1, MS 92-3, 1191100241, ATCC13884 and KCTC-2242 genomes. Here we identified a conserved genetic context and gene synteny of nifJ-nifQ operon both in K. variicola and K. quasipneumoniae genomes (data not shown).…”
Section: In Silico Analysis and Prevalence Of Fimbrial Fimv Proteinmentioning
confidence: 99%
“…In this work, we identified another K. pneumoniae genome (from KPNIN29) that contains the nif operon in addition to that described by Holt and colleagues. 13 Hazen and colleagues 27 identified the absence of nifJ-nifQ gene cluster in K. pneumoniae NTUH-K2044, MGH-78578, 1162281, JH1, MS 92-3, 1191100241, ATCC13884 and KCTC-2242 genomes. Here we identified a conserved genetic context and gene synteny of nifJ-nifQ operon both in K. variicola and K. quasipneumoniae genomes (data not shown).…”
Section: In Silico Analysis and Prevalence Of Fimbrial Fimv Proteinmentioning
confidence: 99%
“…genomes that corresponded to K. variicola and K. quasipneumoniae Both K. variicola as K. pneumoniae and K. quasipneumoniae isolates exhibit very similar biochemical features, 1 and to date there are no reported biochemical tests for their appropriate differentiation. 3,4,10,11 The phylogenetic analysis of the rpoB gene is more adequate than the 16S rRNA for Klebsiella spp. differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…genomes was first identified by whole-genome and rpoB phylogenies. 3,4 Subsequently by K. quasipneumoniae and other K. variicola genomes the misclassification was evidenced by Average Nucleotide Identity (ANI). 5 The aim of this work was detect misclassified K. variicola and K. quasipneumoniae genomes.…”
Section: Artículo Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…The FOX-1 AmpC ␤-lactamase was first detected in a Klebsiella pneumoniae strain isolated from a hospital in Buenos Aires, Argentina, in 1989 (7). Since the initial description of FOX-1, there have been 10 bla FOX alleles characterized to date that have been designated allele numbers by the Lahey Clinic (http://www.lahey.org/Studies/) (7)(8)(9)(10)(11)(12)(13)(14). A recent study demonstrated that the bla FOX-1 gene was associated with an approximately 45-kb plasmid that could be conjugally transferred to an Escherichia coli laboratory isolate (7).…”
mentioning
confidence: 99%